Risk factors and incidence of Macular Edema in eyes with retinal Vein Occlusion after uneventful cataract surgery: The MEVO study - Sagnik Sen; Sourav Damodaran; Prithviraj Udaya; Rachana Mallidi; Chandralakshmi Chandrasekar; Muthukrishnan Vallinayagam; Renu P Rajan; Karthik Kumar; Madhu Shekhar; Naresh Babu Kannan; Kim Ramasamy (Indian Journal of Ophthalmology, 2025)
Purpose: The current study aims to assess incidence of postoperative macular edema (PME), risk factors behind PME and outcomes after cataract surgery in eyes with retinal vein occlusion (RVO). Methods: This retrospective study included 162 eyes of 162 RVO patients, who underwent cataract surgery between 1 January 2015 and 31 December 2019. Eyes with RVO which did not have cystoid macular edema (CME) on optical coherence tomography (OCT) within the immediate 1 month prior to surgery were included. Results: Patients were followed up for an average duration of 13 ± 10.9 months after cataract surgery (range, 6–60 months). The mean time to PME development was 1.87 ± 1.7 months. Postoperative macular edema developed within 3 months after surgery in 40.1% of all eyes, 21% eyes with no previous CME, 57.3% of eyes with previous CME, and in 50% of eyes of patients with diabetes. Significant risk factors of PME identified were diabetes (OR = 2.1) and previous CME (OR = 4.62) requiring treatment with anti-VEGF (OR = 4.83). The visual acuity (VA) of operated eyes significantly improved from 0.85 ± 0.55 logMAR at baseline to 0.365 ± 0.39 logMAR (P<0.0001) at the final follow-up. A significant proportion of eyes showed improvement of their VA beyond Snellen 6/12 at final follow-up (P < 0.0001); however, eyes with PME had a higher chance of poorer vision gain (worse than 6/18). Poor prognostic factors for vision were presence of PME, previous CME and treatment history with injections, central RVO and poor VA at baseline. Conclusion: The study demonstrates that RVO eyes with previous CME requiring intravitreal treatment are at significant risk of postoperative macular edema after uneventful cataract surgery, and this risk increases in people with diabetes. The incidence is not affected by the type of RVO. Considering almost 2/3rd of PME developed within the 1st month of surgery, we recommend a routine OCT scan as a part of postoperative assessment at the 1st visit after surgery, in eyes at risk. Eyes developing PME may have poorer visual outcomes, especially eyes with CRVO; hence, patients need to be counseled carefully regarding outcomes of cataract surgery. The outcomes might depend on the previous treatment course they have received, and they may need to undergo a repeat cycle of treatment due to a risk of return of macular edema.